2012
DOI: 10.1105/tpc.111.094144
|View full text |Cite|
|
Sign up to set email alerts
|

Effective Small RNA Destruction by the Expression of a Short Tandem Target Mimic in Arabidopsis

Abstract: MicroRNAs (miRNAs) and other endogenous small RNAs act as sequence-specific regulators of the genome, transcriptome, and proteome in eukaryotes. The interrogation of small RNA functions requires an effective, widely applicable method to specifically block small RNA function. Here, we report the development of a highly effective technology that targets specific endogenous miRNAs or small interfering RNAs for destruction in Arabidopsis thaliana. We show that the expression of a short tandem target mimic (STTM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
371
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 360 publications
(390 citation statements)
references
References 35 publications
17
371
0
2
Order By: Relevance
“…Moreover, the expression level of miR160 was decreased markedly (Fig. 3E), in agreement with the previous report that some eTMs can induce miRNA degradation (Todesco et al, 2010;Ivashuta et al, 2011;Banks et al, 2012;Yan et al, 2012).…”
Section: Expression Analysis Of Etmssupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, the expression level of miR160 was decreased markedly (Fig. 3E), in agreement with the previous report that some eTMs can induce miRNA degradation (Todesco et al, 2010;Ivashuta et al, 2011;Banks et al, 2012;Yan et al, 2012).…”
Section: Expression Analysis Of Etmssupporting
confidence: 92%
“…4, B and C), as well as accelerated flowering time (data not shown). These phenotypes resembled those of plants overexpressing artificial miR160 target mimics (Todesco et al, 2010;Yan et al, 2012). Correspondingly, the expression of known miR160 target genes was also significantly increased in the osa-eTM160-3 overexpression plants (Fig.…”
Section: Expression Analysis Of Etmssupporting
confidence: 54%
See 2 more Smart Citations
“…Regardless of their origin, the presence of low-abundance sequences raises the question of their biological relevance. miRNA depletion experiments have been carried out for conserved or highly conserved families, and have shown that such families play relevant roles during plant development 42,43 . However, depletion of low-abundance, non-conserved miRNA families has not yet been performed.…”
Section: Resultsmentioning
confidence: 99%